2017
DOI: 10.1007/s12640-017-9848-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Neuroinflammatory Response and Histopathological Alterations Caused by Quinolinic Acid Administration in the Striatum of Glutaryl-CoA Dehydrogenase Deficient Mice

Abstract: Glutaric acidemia type I (GA I) is an inherited neurometabolic disorder caused by a severe deficiency of the mitochondrial glutaryl-CoA dehydrogenase (GCDH) activity. Patients usually present progressive cortical leukodystrophy and commonly develop acute bilateral striatal degeneration mainly during infections that markedly worse their prognosis. A role for quinolinic acid (QA), a key metabolite of the kynurenine pathway, which is activated during inflammatory processes, on the pathogenesis of the acute striat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Otherwise, QA provoked extensive vacuolation and edema in Gcdh‐/‐ mice striatum. A further study showed that QA enhanced CD3 staining and the number of YNO2 positive cells in these animals, implying T lymphocyte infiltration and nitrosative stress, respectively (Amaral et al, 2018). Synergistic toxic effects of QA and GA in neuronal cultures, co‐cultures and mixed cultures from WT rat cerebral cortex and striatum has been also recently described, strengthening a synergistic role of QA and GA in GA I neurodegeneration (Pierozan et al, 2018; Kotlar et al, 2019).…”
Section: Oxidative Stress and Neuroinflammation In Gcdh−/− Micementioning
confidence: 94%
“…Otherwise, QA provoked extensive vacuolation and edema in Gcdh‐/‐ mice striatum. A further study showed that QA enhanced CD3 staining and the number of YNO2 positive cells in these animals, implying T lymphocyte infiltration and nitrosative stress, respectively (Amaral et al, 2018). Synergistic toxic effects of QA and GA in neuronal cultures, co‐cultures and mixed cultures from WT rat cerebral cortex and striatum has been also recently described, strengthening a synergistic role of QA and GA in GA I neurodegeneration (Pierozan et al, 2018; Kotlar et al, 2019).…”
Section: Oxidative Stress and Neuroinflammation In Gcdh−/− Micementioning
confidence: 94%
“…After the administration, the syringe was left in place for an additional 30‐s period and then slowly withdrawn. The dose of QA used was based on previous studies (Amaral et al., 2018; Seminotti et al., 2016). According to the treatment and the diet received, the animals were divided into six final groups as follows: Gcdh +/+ ‐Lys‐V group, Gcdh +/+ ‐Lys‐QA group, Gcdh −/− ‐Lys‐V group, Gcdh −/− ‐Lys‐QA group, Gcdh −/− ‐N‐V group; and Gcdh −/− ‐N‐QA group.…”
Section: Methodsmentioning
confidence: 99%
“…Since QA cannot cross the blood-brain barrier (BBB), it is usually administered in the striatum. QA causes striatal neurodegeneration by excitotoxicity in rats [ 68 ], mice [ 69 ], and primates [ 70 ], like in human HD [ 71 ], and although it does not affect interneurons, it induces astrogliosis [ 72 ] and motor and cognitive symptoms [ 73 ] similar to those of HD.…”
Section: Hd Rodent Modelsmentioning
confidence: 99%
“…Non-genetic models reproduce increased GFAP expression in the striatum. Intrastriatal administration of QA induces astrogliosis in the striatum of rats [ 68 , 72 ] and mice [ 69 ]. Likewise, the intraperitoneal administration of 3NP induces higher GFAP immunoreactivity in the striatum of rats [ 105 - 109 ] and mice [ 110 , 111 ], although when the 3NP dose is high, it kills neurons and astrocytes so that the lesion zone lacks GFAP staining while the marginal area shows increased GFAP immunoreactivity [ 106 ].…”
Section: Hd Rodent Modelsmentioning
confidence: 99%